The Poetic Linguistic Non-Standardness and Meaning Construction: Semantic Aspects of the Associative Theory of Linguistic Creativity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The paper focuses on the role of verbal associations in non-conventional meaning construction. The Associative Theory of Linguistic Creativity is put forward as an attempt to explain the dynamic process of meaning construction in cases of deliberate language nonconformity in poetry. Linguistic creativity of the poet is regarded as de-canonized speech practice, i. e. the deliberate violation of language norm and convention aimed at producing some pragmatic effects. The poet’s lingua-creative innovations and modifications are described in this paper as prompts for the reader’s novel and unique conceptualization. The reader’s construction of meaning of the poet’s linguistic non-standardness is analyzed as re-processing of formal and semantic aspects of linguistic units and modeling of specific associative context of word functioning. Transformations of the word’s associative potential as the prime mover of verbal routine transfigurations are analyzed with regard to the semantic contribution of coresense and consense properties of linguistic units. To illustrate linguistic and conceptual associative transformations, the authors inspect the meaning construction of nonce-words in Lyn Hejinian’s poems. It is demonstrated how the reader processes schematic semantic content and detailed semantic content employing the mechanisms of associative contrast. The complicated relations between non-standard linguistic form, its semantic subject matter and conceptual content are explained from the perspective of associative shifting which broadens the semantic potential of the word and results in developing a sophisticated network of unique conceptual packets of new, emergent meaning.